Investigation of chromium, copper, iron, lead, zinc, and nickel levels in some aquatic organisms in Iloilo City. - Harder, Jerome F. (2004.)
Investigation on the presence and levels of nickel, zinc, lead, copper, chromium, and iron in some aquatic organisms gave a good picture of the present state of metal contamination of organisms in the Iloilo River. Lead and chromium were below the detection limits of the instrument used (0.05 ug/L and 0.02 ug/L, respectively). Iron level was found high especially in gree algae (1.15 x10 raised to the 3rd power - 1.32x10 raised to 3rd power). zinc leves of most invertebrates exceeded the baseline limit set by the International Proagramme on Chemical Safety. Nickel concentrations were generally below the toxic levels except in green algae (1.13x10 raise to the 3rd power ug/g-2.94x10 raise to the 3rd power ug/g)., The visceral organs of the fish contained high concentrations of iron, copper, and zinc because of the physiological role in ingestion, absorption and excretion. However, bivalves as filter feeders accumulated high levels of nickel, iron, copper, and zinc. On the other hand, algae generally contained higher levels of metals than the mangrove plant.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Aquatic Organisms -- Iloilo River